2021
DOI: 10.3390/cells10010117
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myeloid Leukemia: A Model Disease of the Past, Present and Future

Abstract: Chronic myeloid leukemia (CML) has been a “model disease” with a long history. Beginning with the first discovery of leukemia and the description of the Philadelphia Chromosome and ending with the current goal of achieving treatment-free remission after targeted therapies, we describe here the journey of CML, focusing on molecular pathways relating to signaling, metabolism and the bone marrow microenvironment. We highlight current strategies for combination therapies aimed at eradicating the CML stem cell; hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 192 publications
0
84
0
5
Order By: Relevance
“…CML is a malignant myeloproliferative disorder characterized by clonal hematopoietic stem cell proliferation [176]. CML is the BCR-ABL1 oncoprotein-positive MPN characterized by the Philadelphia (Ph) chromosome's presence.…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%
“…CML is a malignant myeloproliferative disorder characterized by clonal hematopoietic stem cell proliferation [176]. CML is the BCR-ABL1 oncoprotein-positive MPN characterized by the Philadelphia (Ph) chromosome's presence.…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%
“…It turns out that the CML stem cells that generate most mature CML cells are responsible for disease relapse post-TKI therapy [ 6 , 7 , 8 ]. While mature CML cells actively proliferate due to BCR–ABL1-dependent signaling, CML stem cells are able to avoid proliferation and maintain quiescence in an oncogene-independent fashion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, much research effort has been devoted to investigating the molecular mechanisms by which CML stem cells exploit stem cell quiescence, and searching for new modes of therapy that can be combined with TKI therapy to eradicate not only mature CML cells but also CML stem cells. Many researchers reported that numerous molecular mechanisms regulate the quiescence and TKI resistance in CML stem cells in vivo [ 6 , 7 , 8 ]. It is reportedly known that several factors within the bone marrow microenvironmental niche are also responsible for the maintenance of self-renewal capacity in CML stem cells in a non-cell autonomous manner [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCR-ABL-related resistance mechanisms, such as point mutations, explain only a minority of the cases of primary resistance to TKIs [ 5 ], but are representative examples of intra-clonal heterogeneity because cells harboring a BCR-ABL mutation are mostly selected by targeted therapy [ 12 ]. Other BCR-ABL-independent mechanisms have been suggested, for example related to the microenvironment [ 13 , 14 ]. Similar to many other cancer types, epigenetic abnormalities also could be involved, notably DNA methylation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%